The Foundations of Scientific Development from the Perspective of the Philosophy of Science - Al Fatih, M.Luthfi; Sari, Efendi; Zalnur, Muhammad (The Future of Education Journal, 2026)
The rapid development of science in the contemporary era demands a deep understanding of its philosophical foundations. This article aims to examine the foundations of scientific development from the perspective of the philosophy of science by analyzing its ontological, epistemological, and axiological dimensions. The research method uses a qualitative approach with a literature review of classical and contemporary philosophy of science texts. The results of the study indicate that the ontological foundation provides an understanding of the nature of the reality studied by science, the epistemological foundation governs the way to acquire valid knowledge, while the axiological foundation determines the values and objectives of scientific development. These three foundations are interconnected and form a comprehensive framework for the responsible development of science. This research reveals that the integration of these three philosophical dimensions is essential to produce knowledge that is not only methodologically valid but also socially and ethically meaningful. The practical implication is the need for a holistic approach in scientific research that considers philosophical aspects alongside technical-methodological ones.